2020
DOI: 10.4300/jgme-d-19-00553.1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Simulation Maximizing the Use of Fresh-Frozen Cadaveric Specimens: Examination of Tissue Integrity Using Ultrasound

Abstract: Background Arthroscopic surgical simulation, including the use of cadaveric tissue, is valuable for training orthopedic surgery residents. However, it is unclear how often fresh-frozen cadaveric tissue can be reused to provide a reproducible model for developing arthroscopic skills. Objective We determined the usefulness of ultrasound in evaluating tissue degradation in fresh-frozen shoulder and knee joints used for surgical simulation. Methods Between February 7 and April 11, 2017, orthopedic residents partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Three studies (Bell et al, 2020; Fernandez‐Gibello et al, 2019; Giussani et al, 2017) reported the use of FFC in ultrasound‐related training. One article reported a pilot study on performing ultrasonography on the brain for neurosurgeons using FFCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies (Bell et al, 2020; Fernandez‐Gibello et al, 2019; Giussani et al, 2017) reported the use of FFC in ultrasound‐related training. One article reported a pilot study on performing ultrasonography on the brain for neurosurgeons using FFCs.…”
Section: Resultsmentioning
confidence: 99%
“…FFCs were evaluated for its suitability in one study (Bell et al, 2020) engaging ultrasound examination. Arthroscopic surgery is an important part of orthopedic surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 4 pelvis through toes specimens are used for pubic symphysis Open Reduction Internal Fixation, then hemisected to provide 8 hemipelvis through toes specimens that can be used twice more in total (but may be sectioned to allow separate uses of foot/ankle vs knee, etc). OHSU has found that cadaveric models can undergo up to 3 freeze/thaw cycles before cremation with acceptable muscle degradation that maintains educational viability 16 .…”
Section: Methodsmentioning
confidence: 99%